Peningkatan Peran Guru Sekolah Dasar Dalam Pengobatan Darurat untuk Menghilangkan Rasa Sakit Gigi dan Mulut - Ryana Budi Purnama; Helmi Hirawan; Tirta Wardana; Mutia Rochmawati; Pratiwi Nur Widyaningsih; Dian Noviyanti; Desi Rachmawati; Rakhmawati Rakhmawati; Shahnaz Dwi Permata Putri; Minda Anita; Kunthi Isri Wulandari; Dani Intan Prabawati (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Abstract - Oral and dental health is a condition that needs to be considered and maintained to improve the quality of life. One of the efforts made to maintain dental and oral health in the school environment is by conducting UKGS (Usaha Kesehatan Gigi Sekolah). In UKGS activities, teachers have a role in providing emergency treatment to relieve pain. The emergency treatment administered by teachers in schools can perform in cases such as avulsions, choking, and abscesses. This community service aims to increase the role of elementary school teachers through UKGS to maintain, improve the oral health of all students at SDN in the Karangtengah area, Baturaden District, Purwokerto. The method of implementation was basely on optimizing the potential of UKGS teacher cadres, including identification of target schools and participants, pre-test implementation, maturation, coaching, enhancement of UKGS teacher cadres. Coaching and training have been carried out for UKGS supervisors for abscess, choking and avelse conditions. Post-test activities to gain insight into emergency medicine and relieve tooth and mouth pain. Results: p data analysis using the Wilcoxon asymp test.sig.(2-tailed) of 0.001 (<0.05), this value indicates that there is an influence on the level of knowledge about emergency medicine. The analysis performed with the Wilcoxon Test; there was a significant difference (sig = 0.001, p <0.05). There was an increase in the average pre-test value of 76.92 and post-test of 97.85.Conclusion: There is increasing knowledge about emergency medicine to relieve tooth and mouth pain in elementary school teachers.